A Review of the Evidence for Corticosteroids in COVID-19. (August 2022) - Johns, Meagan; George, Stephy; Taburyanskaya, Margarita; Poon, Yi Kee
Objective: To review available evidence on corticosteroids in acute respiratory distress syndrome (ARDS), Coronavirus Disease 2019 (COVID-19), and other viral pneumonias. Data Sources: A literature search of MEDLINE, PubMed andclinicaltrials.gov was performed to identify studies between 1980 to 2020 using the following search terms: corticosteroids, COVID19, severe respiratory syndrome coronavirus 2 (SARS-CoV-2), Middle East respiratory syndrome-related coronavirus (MERS-CoV), and influenza. Pre-printed articles were also reviewed atmedRxiv.org . Data Analysis: Corticosteroids were not recommended early in the COVID-19 pandemic outside of the use for concomitant indications (i.e. ARDS, septic shock) as they have been associated with delayed time to viral clearance in other viral pneumonias. A randomized trial showed a mortality benefit with dexamethasone in COVID-19. Guidelines have been updated to include a strong recommendation for their use in COVID-19 in those hospitalized requiring supplemental oxygen or mechanical ventilation. Conclusion: Based on data from available randomized trials, patients that require respiratory support or mechanical ventilation benefit from corticosteroid therapy. Corticosteroids are an inexpensive and readily available therapy that should be standard of care in hospitalized COVID-19 patients requiring respiratory support.